Cloning, expression, and enzymatic activity analysis of strawberry S-adenosyl-L-metnionine synthetase gene FaSAMS1 - Wang, Shu-Fang; Hua, Li-Na; Liu, Xiaofeng; Shen, Yuanyue (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
The S-adenosyl methionine synthetase gene FaSAMS1 is involved in the regulation of strawberry fruit ripening, however, the biochemical properties of FaSAMS1 protein remain unclear. Here, a coding cDNA sequence of FaSAMS1 was cloned by RT-PCR and inserted into a recombinant yeast expression vector pPICZA, then transformed into the yeast expression strain X-33. The fusion protein FaSAMS1 was induced, expressed, and purified. The enzymatic activity analysis of FaSAMS1 showed that the reaction system contains 0.09 mg of FaSAMS1, protein concentration reached at 0.454 mg·mL-1, the activity of the enzyme was 0.32 U, specific activity was 3.56 U·mg-1. This study has provided biochemical evidence for the involvement of ethylene in the regulation of strawberry fruit ripening.